IMPLEMENTASI METODE TIKRAR DALAM MENINGKATKAN KEMAMPUAN MENGHAFAL SISWA PADA PROGRAM TAHFIDZUL QUR’AN SISWA KELAS IX MTs DARUL AMIEN JAJAG GAMBIRAN BANYUWANGI - Mashuri, Imam; Muftiyah, Al; Nafisah, Siti Fiadhiatun (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2022)
This paper is the results of study at Islamic Junior High School with Tahfidzul Qur’an as its program which the goal of this study is for answering three main questions, such as: How the implementation of tikrar method in improving students’ memorizing ability in the Tahfidzul Qur’an program, what are the support and obstacle factors in the tikrar method implementation in order to improve the students’ memorizing ability of Tahfizul Qur’an program, and what solutions are needed to overcome the obstacles in the tikrar method implementation for improving students’ memorizing ability of Tahfidzul Qur’an program. This study is a qualitative type that took descriptive data in the form of words or direct interview with the headmaster of school, the responsible teacher/tahfidz teacher, and some MTs Darul Amien’ students by supporting from the results of documentations and observations. In the other hand, the researcher used data reduction, data display, and conclusion withdrawal as analysis data techniques. Then, it is ended by checking the validity of the researcher’s data using source triangulation. The results of this study are: 1) The planning step in tikrar method implementation at MTs Darul Amien obligates the students to obey the Tahfidzul Qur’an program, creates students with good Qur’an recitement, prepares target of memorizing, determines method used in Tahfidzul Qur’an program and prepares learning tools such as lesson plans, attendance, and assessment journals. Meanwhile, the implementation activity: Begun by praying together, reading (Bin-Nadhor) or muroja’ah together, submitting memorization to the tahfidz teacher in turns, the students were listening into (sima’-menyima’) memorization between friends. Tikrar method it self is implemented by: Reading (Bin’Nadhor) repeatedly, correcting the Qur’an recitement, memorizing the verse by verse until fluently, submitting memorization to tahfidz teacher, repeating memorization (morojo’ah) repeatedly, and combining new memorization and old memorization. Next, for the evaluations are included from two forms of evaluations, they are evalution for letter/juz increasing and evaluation for graduating. 2) Supporting factors: The condusive atmosphere, have an accurate reciting, friends of the same age, motivation, and unchangeable mushaf. In the other hand, there are two types of inhibiting factor from the internal factors are: desire to increase memorization without paying attention to previous memorization, feeling lazy and bored because of the busy activities, difficult to memorize which can be caused by a low IQ level. The external factors are: similar verses and complex surahs of Al-Qur’an, and busyness because of islamic boarding activities. 3) Solutions for students: increasing the reciting enthusiasm by continuing to recite and memorize, managing the time between memorizing Al-Qur’an and nadhoman, and requesting some reliefs to friend or senior for listening into the memorization. Solutions which can be done by tahfidz teacher: such as by giving a special attention for students who have lower IQ by dividing them into many groups according to their ability and carry out special supervision in order to make their memory in reciting controllable.